Elanela Rolston revisited (Heteroptera: Pentatomidae): new distributional records and description of new species - Grazia, Jocelia; Barros, Lurdiana Dayse De; Barão, Kim Ribeiro (Zootaxa, 2016)
Menidini is highly diverse in the Paleartic and Afrotropical regions. Only two genera, Rio Kirkaldy and Elanela Rolston, are currently known from the Neotropical region. Here we describe five new species of Elanela: E. nigrofemorata sp. nov., E. diamphidiosa sp. nov., E. rafaeli sp. nov., E. fernandesi sp. nov., and E. scutomaculata sp. nov. The generic diagnosis of Elanela is modified to accommodate the new species and a dichotomous key is provided.